Evaluating The Impact of Digital Marketing Strategies on Enrollment Decisions through PLS-SEM Analysis: Insights from Private University X - Syunita, Zahra Raniah Putri; Tikno, Tikno (Diponegoro University, 2025)
This study evaluates the effectiveness of digital marketing strategies in influencing enrollment decisions at Indonesian private universities. With the increasing reliance on digital platforms, higher education institutions (HEIs) have adapted their marketing approaches to engage digitally-savvy prospective students. The aim of this research is to identify the most impactful strategies and their contribution to student enrollment decisions. Utilizing Partial Least Squares Structural Equation Modeling (PLS-SEM), the study compares three models: one derived from prior research and two newly proposed by the authors. Data collected from 325 respondents revealed that social media engagement and personalized direct messaging significantly enhance enrollment decisions, with the highest R² value (0.772) observed for social media engagement in Model 2. The Bayesian Information Criterion (BIC) indicated Model 2 as the best fit (-255.774) for explaining enrollment decisions. These findings suggest that strategies emphasizing social media engagement and personalized communication yield the greatest impact on prospective students. This study contributes to the growing field of digital marketing in higher education by offering actionable insights for enhancing online visibility and optimizing enrollment outcomes in a competitive market.